Daidzein improves muscle atrophy caused by lovastatin by regulating the AMPK/FOXO3a axis - Keke Wang; Hao Zeng; Hua Yang (Chinese Medicine)
Abstract Background Lovastatin, the main lipid-lowering component in red yeast rice, is a golden anti-lipid drug, but its long-term application is continuously challenged by potential skeletal muscle atrophy. Daidzein, an isoflavone derived from soybeans and many Chinese medicines, shows therapeutic potential in treating muscle-related diseases and metabolic disorders. However, whether daidzein can improve lovastatin-induced muscle atrophy and the specific mechanism needs to further study. Methods Lovastatin-induced mice and zebrafish muscle atrophy models were used to validate the protective effect of daidzein in vivo. And the lovastatin-induced C2C12 myotube atrophy model was employed to validate the therapeutic efficacy and investigate the specific mechanism of daidzein in vitro. We combined specific siRNA targeting FOXO3a and AMPK-selective inhibitor, agonist to elucidate AMPK/FOXO3a-dependent muscle-protective mechanism of daidzein. The anti-atrophy effects of daidzein through blockage of abnormal activation of AMPK/FOXO3a was presented in Immunofluorescence, H&E staining, Western blot, qRT-PCR. Serum creatine kinase level was detected by ELISA and we used mouse muscle grip instrument to detect the strength of mouse muscles. Results In this study, we demonstrated that daidzein could dose-dependently alleviate lovastatin-induced mice skeletal muscle atrophy, reduce serum creatine kinase, and improve muscle grip strength in mice. Mechanistically, daidzein inhibited lovastatin-induced FOXO3a phosphorylation caused by AMPK activation, thereby inhibiting FOXO3a nuclear translocation to restrain the expression of muscle-related proteins Atrogin-1 and MuRF-1. In C2C12 myotube, administration of AMPK-selective inhibitor Compound C recapitulated the therapeutic effects of daidzein against lovastatin-induced myotubes atrophy, while the anti-atrophy effects of daidzein were lost in the presence of AMPK-selective agonist MK-3903. In lovastatin-induced mice muscle atrophy models, Compound C elicited similar anti-atrophy effects as daidzein, but this effect was not potentiated when it was applied in combination with daidzein, suggesting that daidzein exerted therapeutic efficacy dependent on blockage of AMPK activity. Conclusions Our study identified daidzein as an effective component that ameliorated lovastatin-induced skeletal muscle atrophy through blockage of abnormal activation of AMPK/FOXO3a and transcriptional activation of genes encoding downstream muscle-related proteins. Our results also highlighted the therapeutic potential by regulating the AMPK/FOXO3a axis in management of statin-induced myotoxicity.